High DNA‐Binding Affinity and Gene‐Transfection Efficacy of Bioreducible Cationic Nanomicelles with a Fluorinated Core. (20th November 2015) - Wang, Long‐Hai; Wu, De‐Cheng; Xu, Hang‐Xun; You, Ye‐Zi
Abstract: During the last two decades, cationic polymers have become one of the most promising synthetic vectors for gene transfection. However, the weak interactions formed between DNA and cationic polymers result in low transfection efficacy. Furthermore, the polyplexes formed between cationic polymers and DNA generally exhibit poor stability and toxicity because of the large excess of cationic polymer typically required for complete DNA condensation. Herein, we report the preparation of a novel class of bioreducible cationic nanomicelles by the use of disulfide bonds to connect the cationic shell to the fluorocarbon core. These bioreducible nanomicelles form strong interactions with DNA and completely condense DNA at an N/P ratio of 1. The resulting nanomicelle/DNA polyplexes exhibited high biocompatibility and performed very effectively as a gene‐delivery system.